Primary Health Care Nurses’ Knowledge about Alcohol Use with Respect to its Impact on Blood Pressure and the Risk of Developing Arterial Hypertension - Grabowska, Hanna; Grabowski, Władysław; Gaworska-Krzemińska, Aleksandra; Grzegorczyk, Michał; Świetlik, Dariusz; Narkiewicz, Krzysztof (Polish Journal of Public Health, 2009)
Introduction. Primary health care (PHC) nurses can play a signifi cant role in reducing the cardiovascular risk, and contribute to lowering alcohol consumption by their patients. Purpose. Determining the knowledge of PHC nurses about alcohol consumption evaluation and its impact on arterial blood pressure (BP) and the risk of developing hypertension. Material and methods. The study, conducted in 2007-2009, included 185 PHC nurses (aged 23-60, x=40.9, SD=7.12; length of service 1-35 years, x=19.37, SD=7.15). The following methods were employed: diagnostic survey, questionnaire technique and custom survey questionnaire. The statistical analysis used the STATISTICA software package, the assumed signifi cance level being p≤0.05. It took into account the effect of age, domicile, job, place and length of service and forms of postgraduate education on the nurses’ knowledge levels. Results. Knowledge of questionnaire screening tools for evaluating alcohol drinking styles was demonstrated by 15.1% of nurses; 37.3% and 53.5% of the respondents, respectively, correctly interpreted the standard portion and pointed to the alcohol consumption limit. The impact of alcohol consumption on BP was known to 91.9% of PHC nurses. Statistically, correct answers were more frequently given by persons who graduated from bachelor’s degree courses in nursing (p<0.001) and those who completed two qualifying courses (p=0.02). The study showed statistically signifi cant differences in correct answers relatively to the subjective evaluation of their own preparation to identify hypertension development risk factors (p=0.03), and the prevention measures declared by the respondents (p=0.004). Age, place of residence, family status, length of service and position had no statistically signifi cant impact on the correctness of answers. Conclusions. The PHC nurses under study presented a moderate level of knowledge about the assessment of risk of hypertension related to alcohol consumption. It is advisable to popularize the knowledge of the discussed issues among PHC nurses more extensively.